Hypnotherapy treatment in a 25 years-old singer with Dysphonia and Sinusitis : A case report - Hutomo, Yudhistira (International Journal Labs, 2024)
Hypnotherapy is a therapeutic modality used to address psychological and behavioral issues by providing positive suggestions to the subconscious mind. This case report discusses a patient presenting with chronic dysphonia and sinusitis. Dysphonia can have multiple causes, including sinusitis, emotional disorders such as trauma, anxiety, and depression, as well as occupational and lifestyle factors. A thorough diagnosis of dysphonia requires comprehensive physical and supportive examinations. Once diagnosed, a holistic treatment approach is essential, combining symptom management, medication, psychotherapy, and speech therapy. In this case, hypnotherapy was used as part of the psychotherapy treatment, leading to significant improvement in the patient's condition. This case highlights the potential benefits of incorporating hypnotherapy in the management of dysphonia.